Phylogenetic analysis of sheep pox virus (SPPV) virion core protein P4a gene revealed extensive sequence conservation among capripox viruses - MISHRA, BINA; KUMAR, G RAVI; SONAL, SONAL; PATEL, C L; CHATURVEDI, V K (The Indian Journal of Animal Sciences, 2018)
In the present study, virion core protein P4a gene was PCR amplified from sheep pox virus (SPPV) Jaipur isolate and Roumanian Fanar (RF) vaccine strain adapted and propagated in lamb testis/vero cells. Gene specific primers were designed for amplification of P4a gene. Amplified P4a gene fragment was sequence characterized and 808 bp sequence was compared across SPPV, GTPV and LSDV isolates available in GenBank database which revealed extensive sequence conservation of 97% to 100% within pox virus groups. Sheep pox virus Jaipur isolate was found closely placed with Roumaninan Fanar (RF) and TU isolates. Further, phylogenetic analysis of P4a gene sequence indicated three distinct clusters of Capripox viruses with GTPV interestingly placed closely to LSDV group.